2019
DOI: 10.1111/jgs.16146
|View full text |Cite
|
Sign up to set email alerts
|

High‐Need Phenotypes in Medicare Beneficiaries: Drivers of Variation in Utilization and Outcomes

Abstract: OBJECTIVES High‐need (HN) Medicare beneficiaries heavily use healthcare services at a high cost. This population is heterogeneous, composed of individuals with varying degrees of medical complexity and healthcare needs. To improve healthcare delivery and decrease costs, it is critical to identify the subpopulations present within this population. We aimed to (1) identify distinct clinical phenotypes present within HN Medicare beneficiaries, and (2) examine differences in outcomes between phenotypes. DESIGN Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…This may be relevant because we found evidence of frailty across all segments-5% of those relatively healthy, 12% of minor complex and 21% of major complex. Also consistent with prior work, we found that HNHC Mexican American older adults have functional limitations and a combination of multiple chronic conditions [3,6,34].…”
Section: Plos Onesupporting
confidence: 91%
“…This may be relevant because we found evidence of frailty across all segments-5% of those relatively healthy, 12% of minor complex and 21% of major complex. Also consistent with prior work, we found that HNHC Mexican American older adults have functional limitations and a combination of multiple chronic conditions [3,6,34].…”
Section: Plos Onesupporting
confidence: 91%
“…HNHC patients also have unmet needs either with their medical care (i.e., difficulty obtaining medication), ADLs (i.e., lack of needed support with bathing or feeding), or other needs related to obtaining housing or nutritional food 15,34 . Patients with unmet needs are more likely to have acute exacerbations of ongoing medical or behavioral conditions and frequent hospitalizations and ED use 10,15,34 . HNHC patients also have high rates of psychosocial factors such as isolation and mental illness which are found to worsen medical conditions and lead to higher health service use and mortality rates 15,35,36 …”
Section: Resultsmentioning
confidence: 99%
“…While HNHC patients are often referred to as the 5% of the population who account for the majority of overall US health care costs, significant heterogeneity exists in the definition of HNHC patients with regard to age, comorbidities, disability, and social needs 1,10 . Additionally, many common characteristics used to describe HNHC patients are implied rather than explicitly stated which can further exacerbate challenges in identifying this population and developing sustainable interventions 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Persons with ADRD have high costs and high needs. 1 Among persons who die with dementia, average Medicare spending in the last 5 years of life is $287,038, exceeding end-of-life spending for other leading causes of death. 2 ADRD patients and their families often experience burdensome and costly interventions at the end of life that may be of limited benefit and not aligned with patients' preferences.…”
Section: Introductionmentioning
confidence: 99%